USM AND PROTON ESTABLISH COLLABORATION IN AUTOMOTIVE ENGINEERING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
NIBONG TEBAL, 18 January 2016 – Universiti Sains Malaysia (USM) Engineering Campus received an 11member delegation visit from PROTON headed by its Professor, Dr. Shuhaimi Mansor here recently.